2011
DOI: 10.1371/journal.ppat.1002020
|View full text |Cite
|
Sign up to set email alerts
|

Engineering HIV-Resistant Human CD4+ T Cells with CXCR4-Specific Zinc-Finger Nucleases

Abstract: HIV-1 entry requires the cell surface expression of CD4 and either the CCR5 or CXCR4 coreceptors on host cells. Individuals homozygous for the ccr5Δ32 polymorphism do not express CCR5 and are protected from infection by CCR5-tropic (R5) virus strains. As an approach to inactivating CCR5, we introduced CCR5-specific zinc-finger nucleases into human CD4+ T cells prior to adoptive transfer, but the need to protect cells from virus strains that use CXCR4 (X4) in place of or in addition to CCR5 (R5X4) remains. Here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
145
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(146 citation statements)
references
References 62 publications
1
145
0
Order By: Relevance
“…Off-target cleavage has been reduced by the development of FokI variants that can function only as heterodimers, thus preventing cleavage by undesired homodimers (176), but questions remain regarding the ultimately achievable specificity of ZFNs. Despite these potential limitations, ZFNs have achieved major successes, having been used extensively in the study of knockout of the HIV coreceptor CCR5 (75,137,204) and more recently to directly target HBV covalently closed circular DNA (cccDNA) in infected hepatocytes (39).…”
Section: Specific Types Of Cleavage Enzymesmentioning
confidence: 99%
See 1 more Smart Citation
“…Off-target cleavage has been reduced by the development of FokI variants that can function only as heterodimers, thus preventing cleavage by undesired homodimers (176), but questions remain regarding the ultimately achievable specificity of ZFNs. Despite these potential limitations, ZFNs have achieved major successes, having been used extensively in the study of knockout of the HIV coreceptor CCR5 (75,137,204) and more recently to directly target HBV covalently closed circular DNA (cccDNA) in infected hepatocytes (39).…”
Section: Specific Types Of Cleavage Enzymesmentioning
confidence: 99%
“…Strategies aimed at both the integrated provirus and cellular genes that permit HIV infection are promising but require enzyme delivery to specific but distinct cell types. ϩ T cells that could engraft upon transplantation into immunodeficient mice (137,204). Nonintegrating lentivirus vectors (also referred to as integrase-deficient lentiviruses [IDLVs]) have also successfully been used to deliver gene-targeted ZFNs to CD34 ϩ cells (104).…”
Section: ϫ5mentioning
confidence: 99%
“…However, the possible appearance of X4-tropic virus in the late stages of the disease requires approaches to engineer HIV-1 target cell resistance to X4-or R5X4-tropic virus. Wilen et al reported partial protection of CXCR4-edited CD4 cells in humanized mice (28). Env sequencing and tropism testing showed that a shift to CCR5 usage by the virus accounted for the depletion of CXCR4-disrupted cells at later time points.…”
Section: Discussionmentioning
confidence: 99%
“…Since the unique and exceptional case of an HIV-1 sterilizing cure of a patient due to bone marrow transplantation with a matched donor homozygote for the CCR5⌬32 mutation (47,48), alternative strategies have aimed to reproduce the CCR5⌬32 phenotype using genome-editing tools. Indeed, ZFNs targeting the HIV coreceptor gene have been successfully developed to generate human CD4 ϩ T cells and human embryonic cell precursors and induce pluripotent stem cells that were refractory to HIV-1 infection in different mouse models (9)(10)(11)(12)(13).…”
Section: Discussionmentioning
confidence: 99%
“…ZFNs have demonstrated their applicability to reproduce the CCR5⌬32 phenotype in vitro by successfully cleaving the CCR5 gene, generating human CD4 ϩ T cells refractory to HIV-1 infection (9)(10)(11)(12). Similarly, a ZFN approach successfully cleaved the alternative HIV-1 coreceptor CXCR4 in CD4 ϩ T cells in a humanized mouse model, resulting in impaired HIV-1 infection (13). Genome editing as anti-HIV therapy is currently under study in at least 2 or 3 clinical trials using ZFNs targeting CCR5.…”
mentioning
confidence: 99%